A Study of Factors Determining the State-Owned Government-Linked Companies' Performance - Wan Izyani Adilah, Wan Mohamad; Wan Amalina, Wan Abdullah@Wan Abdullah; Noryati, Yaakub (2014)
The transformation program of Government-Linked Companies (GLCs) in 2006 was aimed at improving the performance of federally-owned Malaysian GLCs. Initiated by Putrajaya Committee on GLC High Performance (PCG), the program has recommended a template and assessment grid for GLCs to determine the effectiveness of their Board of Directors. The present study attempts to examining the applicability of these mechanisms to the state-owned GLCs by examining the relationship between the board structure and the financial performance of state GLCs. A sample of 18 state-owned GLCs in Malaysia were studied using their published 2012 annual reports. Five corporate governance variables were examined: (i) the size of the board; (ii) the proportion of independent directors on board; (iii) the financial literacy of directors (iv} the multiple directorships; and (v) the frequency of meetings. A correlation analysis was conducted to preliminary assess the above relationships. Based on the analysis, factors identified to have associations with state GLCs' performance are board size and multiple directorships. The study is hoped to fill the gap in literature on corporate governance as well as to provide insights for standard setters, on the board effectiveness in state GLCs.